eCM 2021
DOI: 10.22203/ecm.v042a12
|View full text |Cite
|
Sign up to set email alerts
|

IgG4-specific responses in patients with Staphylococcus aureus bone infections are not predictive of postoperative complications

Abstract: The most prevalent pathogen in bone infections is Staphylococcus aureus; its incidence and severity are partially determined by host factors. Prior studies showed that anti-glucosaminidase (Gmd) antibodies are protective in animals, and 93.3 % of patients with culture-confirmed S. aureus osteomyelitis do not have anti-Gmd levels > 10 ng/mL in serum. Infection in patients with high anti-Gmd remains unexplained. Are anti-Gmd antibodies in osteomyelitis patients of the non-opsonising, non-complement-fixing IgG… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
2
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(4 citation statements)
references
References 33 publications
(57 reference statements)
1
2
1
Order By: Relevance
“…Furthermore, low anti-Gmd titer patients have a highly significant 2.7-fold increased risk in adverse outcomes within 1 year of surgery ( Kates et al., 2020 ). However, in contrast to our hypothesis of passive immunization with anti-Gmd mAb, we found that a few patients had high titers of anti-Gmd antibodies at baseline and had adverse outcomes following surgery, which was not due to IgG4 class switching to non-functional immunoglobulin ( Owen et al., 2021 ). Thus, we aimed to determine if this was due to non-neutralizing antibodies.…”
Section: Discussioncontrasting
confidence: 99%
See 3 more Smart Citations
“…Furthermore, low anti-Gmd titer patients have a highly significant 2.7-fold increased risk in adverse outcomes within 1 year of surgery ( Kates et al., 2020 ). However, in contrast to our hypothesis of passive immunization with anti-Gmd mAb, we found that a few patients had high titers of anti-Gmd antibodies at baseline and had adverse outcomes following surgery, which was not due to IgG4 class switching to non-functional immunoglobulin ( Owen et al., 2021 ). Thus, we aimed to determine if this was due to non-neutralizing antibodies.…”
Section: Discussioncontrasting
confidence: 99%
“…Results from clinical research to define native humoral immunity against S. aureus in osteomyelitis patients also supports the hypothesis that passive immunization with anti-Gmd mAb may be an effective treatment ( Gedbjerg et al., 2013 ; Oh et al., 2018 ; Kates et al., 2020 ; Owen et al., 2021 ). Most notable are the results from the AOTrauma CPP Bone Infection Registry, which showed that only 6.7% of patients with life-threatening S. aureus osteomyelitis have basal levels of anti-Gmd antibodies (>10 ng/ml) in their serum at the time of surgery, and that for every 10-fold increase in anti-Gmd antibody concentration in sera, there is a 60% reduction in adverse event risk ( Kates et al., 2020 ).…”
Section: Discussionsupporting
confidence: 56%
See 2 more Smart Citations